2021
DOI: 10.1097/phh.0000000000001322
|View full text |Cite
|
Sign up to set email alerts
|

The Supply and Distribution of the Preventive Medicine Physician Workforce

Abstract: Context: Preventive medicine physicians work at the intersection of clinical medicine and public health. A previous report on the state of the preventive medicine workforce in 2000 revealed an ongoing decline in preventive medicine physicians and residents, but there have been few updates since. Objective: The purpose of this study was to describe trends in both the number of board-certified preventive medicine physicians and those physicians who self-designate preventive medicine as a primary or secondary spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…More than half of both graduates and residents identified as female, a higher percentage than historical studies reporting a range of 32–36% ( Salive and Parkinson, 1991 , Salive, 1997 , Liang et al, 1995 ). The higher female response rate in our survey may reflect recent nationwide trends of increasing number of females attending medical school ( The Majority of U.S. Medical Students Are Women, New Data Show ); and appears to be in keeping with data reported by a recent survey of PM residents ( Ricketts et al, 2021 ). Approximately 16 % of our participants were International Medical Graduates (IMGs), similar to the 13% active PM IMGs reported in the American Association of Medical Colleges 2020 physician specialty data report ( Active Physicians Who Are International Medical Graduates (IMGs) by Specialty, 2019 ).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…More than half of both graduates and residents identified as female, a higher percentage than historical studies reporting a range of 32–36% ( Salive and Parkinson, 1991 , Salive, 1997 , Liang et al, 1995 ). The higher female response rate in our survey may reflect recent nationwide trends of increasing number of females attending medical school ( The Majority of U.S. Medical Students Are Women, New Data Show ); and appears to be in keeping with data reported by a recent survey of PM residents ( Ricketts et al, 2021 ). Approximately 16 % of our participants were International Medical Graduates (IMGs), similar to the 13% active PM IMGs reported in the American Association of Medical Colleges 2020 physician specialty data report ( Active Physicians Who Are International Medical Graduates (IMGs) by Specialty, 2019 ).…”
Section: Discussionsupporting
confidence: 81%
“…A recent study by Ricketts et al found <50% of physicians who self-identified as a PM specialist had PM board-certification ( Ricketts et al, 2021 ). In their study, they also reported difficulty in assessing the current PM workforce due to the absence of a clear established definition of the PM specialty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These authors concluded, "There is extremely little penetration of the PM workforce into rural areas." 3 There is therefore not only a growing national shortage of PM physicians but also a maldistribution.…”
mentioning
confidence: 99%